Pembuatan website sebagai Pengenalan Wisata Budaya di Desa Giring - Prijowuntato, S. Widanarto; Krissandi, Apri Damai Sagita; Nugroho, Robertus Adi (JURNAL DESTINASI PARIWISATA; Vol 9 No 1 (2021): VOL 9, NO 1 (2021): (JANUARY-JUNE) JURNAL DESTINASI PARIWISATA, 2021)
The history of the village of giring is closely related to the history of Yogyakarta. Therefore, in the village of Giring there are various interesting cultural and historical heritage sites. Currently, few tourists are willing to visit these cultural sites. This study aims to develop a tourism website for the village of Giring. The study was carried out using the following steps: analyzing needs, gathering information, designing the web, improving the design, conducting trials, and uploading the web. This research uses a research and development approach. Data collection using tests and questionnaires. The research data were analyzed quantitatively and qualitative. The results showed that the website developed was feasible to use based on the trial results. This website is considered useful for introducing the many cultural and traditional potentials of Giring Village. The website contains various cultures and traditions as well as traditional games that develop in society. Visitors can enjoy various religious sites that contain interesting stories about Ki Ageng Giring. Keywords: website, cultural tourism, Giring